2001
DOI: 10.1128/iai.69.2.695-705.2001
|View full text |Cite
|
Sign up to set email alerts
|

Serum Resistance in an Invasive, NontypeableHaemophilus influenzaeStrain

Abstract: A common feature of many different organisms causing bacteremia is the ability to avoid the bactericidal effects of normal human serum. In Haemophilus influenzae encapsulated strains are particularly serum resistant; however, we found that a nonencapsulated strain (R2866) isolated from the blood of an immunocompetent child with meningitis who had been successfully immunized with H. influenzae type b conjugate vaccine was serum resistant. Since serum resistance usually involves circumventing the action of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 31 publications
1
47
1
Order By: Relevance
“…These data suggest that complement inhibition in R2866 occurs at or before the step of C4 binding. We were unable to detect differences in IgG (total IgG and IgG subclasses) or IgM binding to both strains Rd KW20 and R2866, which suggests that differences in the amount of Ab binding are not responsible for differences in C4b deposition (16). Furthermore, we did not observe in either strain binding to lectin pathway activators (mannose binding lectin and ficolins) or recruitment of complement regulatory proteins C4b-binding protein and C1-esterase inhibitor (data not shown).…”
Section: R2866 Delays C4b Depositionmentioning
confidence: 55%
See 3 more Smart Citations
“…These data suggest that complement inhibition in R2866 occurs at or before the step of C4 binding. We were unable to detect differences in IgG (total IgG and IgG subclasses) or IgM binding to both strains Rd KW20 and R2866, which suggests that differences in the amount of Ab binding are not responsible for differences in C4b deposition (16). Furthermore, we did not observe in either strain binding to lectin pathway activators (mannose binding lectin and ficolins) or recruitment of complement regulatory proteins C4b-binding protein and C1-esterase inhibitor (data not shown).…”
Section: R2866 Delays C4b Depositionmentioning
confidence: 55%
“…Our initial studies suggested that delayed C3 deposition mediates serum resistance in strain R2866 and that a functional CP is required for complement activation (16). We hypothesized that complement inhibition on R2866 occurred between the initiation of CP activation and C3 deposition.…”
Section: R2866 Delays C4b Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unencapsulated strains, such as Rd KW20 (R652), are relatively serum sensitive compared with capsule-producing strains (e.g. Eagan), which can replicate in 50 % NHS and whole blood, or the rare serum-resistant non-typable strain INT-1 (R2866) ( Table 3) (Williams et al, 2001). In the serumresistance assay, the reported IC 50 was the mean (±SD) concentration of serum required to kill 50 % of the inoculum within a 30 min incubation period (Table 3).…”
Section: Resistance To the Bactericidal Activity Of Nhsmentioning
confidence: 99%